Analysis of the availability of bronchodilators and anti-inflammatory drugs for patients with chronic obstructive pulmonary disease - E. A. Orlova; V. I. Petrov; I. P. Dorfman; O. V. Shatalova; M. A. Orlov (IRBIS LLC, 2024)
Background. The study of drug availability for patients with chronic obstructive pulmonary disease (COPD) represents one of the priority tasks in the organization of effective counteraction to COPD in the Russian Federation.Objective: to assess drug prices, affordability, and availability for COPD patients.Material and methods. The analysis of drug availability for COPD patients was carried out according to the methodology of the World Health Organization and Health Action International (WHO/HAI). Bronchodilator and anti-inflammatory therapy of originator brands and lowestpriced generics was evaluated. The consumption volume of the studied drugs was also analyzed using the ATC/DDD (Anatomical Therapeutic Chemical classification / defined daily dose) pharmacoepidemiologic methodology over a three-year period (from 2020 to 2022), taking into account their share of total DDD (drug utilization analysis, DU90%).Results. According to the results of DU90% analysis, the most purchased drugs for bronchodilator and anti-inflammatory therapy for all the years under study were drugs from the groups of short-acting bronchodilators (salbutamol, fenoterol, ipratropium bromide + fenoterol) and inhaled glucocorticoids (budesonide, beclomethasone). The obtained data were confirmed by the results of the physical availability study. Thus, the highest percentage of physical availability was for short-acting inhaled beta-2-agonists (SABA) (salbutamol). Analysis of drug affordability also revealed a tendential superiority of SABA and short-acting anticholinergics over baseline bronchodilators and antiinflammatory drugs.Conclusion. Low affordability of the main drugs of baseline therapy contributes to the burden of COPD and necessitates improvement of drug supply mechanisms for individuals, especially those with low material income, which in the long term will significantly reduce the costs of the healthcare system for the treatment of these patients by decreasing the severity and frequency of exacerbations.